A RESEARCH ON MALE AND FEMALE FIGURES IN THE ELEMENTARY SCHOOL TEXTBOOKS - Yasemin ESEN; Melike Türkan Bağlı (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The aim of the study was to evaluate adult figures on the pictures in the Turkish and Alphabet textbooks for elemantary schools, grade 1. The adult figures were examined in terms of their actions, people whom they were presented with, places where they were shown, objects which they were connected with. Results of the study revealed that both men and women were presented with “children” mostly; the women were shown at “home and home environments” while the men were presented at “outdoors”. On the pictures, the women were shown mostly while they were in the actions “related with children”; on the other hand, the men were in the actions “related with public and work.” The pictures also showed that the women were connected with “private” objects while the men were connected with “public” ones. The findings of the study showed that gender stereotypes have been transfered to children through textbooks as well as the whole educational system